Localization protocols for mobile wireless sensor networks: A survey. (October 2018) - Chelouah, Leila; Semchedine, Fouzi; Bouallouche-Medjkoune, Louiza
Abstract: Wireless Sensor Networks (WSNs) were emerged with the recent advances in the field of micro-electronics and the emergence of wireless communication technology. Although, it has been shown that mobility alleviates several issues relating to sensor network like the coverage optimization and the connectivity. The need for node localization is one of the most important challenges when considering mobility. Localization in WSN means estimating the position or spatial coordinates of nodes. This paper addresses the various issues in localization and presents the state of the art of localization algorithms in Mobile WSNs (MWSNs). In this paper, we classified the localization algorithms based on the localization technique, the anchor based/cooperative, the nodes' mobility state and the information state and, we presented a detailed analysis of the representative localization algorithms. Moreover, we compared the existing localization algorithms and we discussed some possible directions of future research for the localization algorithms in MWSNs.